Glass production from rice husk ash as an imitation gemstone products. (2022) - Ravangvong, S.; Khunnarong, S.; Temmawat, S.; Chaichalerm, S.; Nissapa, W.; Pinnak, K.; Sriumnuay, B.; Sriwongsa, K.; Glumglomchit, P.; Boonsang, P.; Ruangtaweep, Y.; Kaewkhao, J.
Abstract: The objectives of this research were study the amount of SiO2 content from naturally burned rice husk ash (RHA) for prepare rice husk ash glass (RHA-glass) from Phetchaburi Province, Thailand, for the development of gemstones and artificial jewelry from colored glass. The naturally burned RHA were re-burned RHA at 400, 500, 600, 700, 800, 900 and 1000 °C and analyzed the composition of various elements in RHA by distributed energy X-ray fluorescence spectrometer. The results found that re-burned RHA at 1000 °C had SiO2 element maximum, so the re-burned RHA at 1000 °C was prepared RHA-glass. In addition, glass sample from naturally burned RHA and re-burned RHA at 1000 °C have been studied density, refractive index and absorbance. For the colored glass samples were prepared using melt quenching technique by doped MnO2, CuO, Cr2 O3, CoO and Er2 O3 elements which according to glass formula 54SiO2 : 1Al2 O3 : 6.3CaO: 0.2Sb2 O3 : 13B2 O3 : 4.5BaO: 20Na2 O: 1A in mol% where A is the type of element added to cause color. The results exhibited that re-burned RHA glass which doped MnO2, CuO, Cr2 O3, CoO and Er2 O3 shown colored brown, light blue, green, deep blue and pink, respectively and potential to use as imitation gemstone which is increasing value of RHA.